Nucleic Acid Immunity in the Pathogenesis of Cutaneous Lupus Erythematosus - Günther, Claudia (Frontiers in Immunology, 2019)
Cutaneous lupus erythematosus can be a devastating painful and mutilating disease that is associated with an inflammatory response in the skin driven by type I interferon activation. Clearance defects in the extra- and intracellular space lead to an enhanced prevalence of nucleic acids that represent danger signals for the innate immune system. Self nucleic acids can stimulate DNA and RNA sensors that have originally evolved to ensure viral defense.. Their activation can induce a type I interferon dominated response in resident skin cells, macrophages and dendritic cells that subsequently progresses to adaptive immune stimulation. The genetic exploration of rare monogenic type I interferon driven diseases helped to identify these pathogenic concepts. Based on a genetic susceptibility lupus patients are more vulnerable to environmental trigger factors such as UV-irradiation that can provoke inflammation with local tissue destruction and eventually systemic disease. Understanding of these pathogenic concepts is a prerequisite for development of targeted therapies.